The reconciliation approach in resolving contradictory prophetic tradition - Rohaizan, Baru; Rosmalizawati, Abd. Rashid (2011)
The issue of the prophetic narrations that seem to contradict one another or contrary to Quranic texts or even other facts have been debated and discussed by the hadith scholars long time ago. The scholars, whom are being referred to, always ready to provide interpretations, explanations and conclusions to resolve these so called ‘contradictions’ which in reality can cause a significant impact on the accountability of hadiths as one of the main sources for the Muslims civilization. Hence, this paper aims to analyse and review the method of al-Jam’ (reconciliation) adopted by the scholars of hadith in addressing and resolving the contradictory of hadiths. One of the dominant and chosen methods in solving this problem is by the reconciliation between the meanings and purposes of the hadiths that appeared to contradict one another